2014
DOI: 10.1161/strokeaha.114.006622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extracranial Carotid Stenosis on Intracranial Blood Flow

Abstract: Background and Purpose— The hemodynamic effects of extracranial carotid stenosis on intracranial blood flow are not well characterized. We sought to determine the impact of degree of stenosis, stenosis length, and residual lumen on intracranial blood flow in patients with extracranial carotid stenosis. Methods— Carotid stenosis patients who had undergone both vessel flow rate measurements using quantitative magnetic resonance angiography and digital sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 10 publications
(6 reference statements)
3
41
2
Order By: Relevance
“…[6][7][8][13][14][15][16][17] Before any treatment, mean WSS among 48 feeder arteries in our study was significantly higher compared with the mean WSS in the contralateral vessel (29.7±12.0 dynes/cm 2 versus 23.3±11.0 dynes/ cm 2 ; P=0.007). This result reveals that cerebral AVMs are a high WSS pathology, which disputes Rossitti and Svendsen's hypothesis that WSS in arteries supplying AVMs is the same as in arteries within normal brain parenchyma.…”
Section: Discussioncontrasting
confidence: 50%
“…[6][7][8][13][14][15][16][17] Before any treatment, mean WSS among 48 feeder arteries in our study was significantly higher compared with the mean WSS in the contralateral vessel (29.7±12.0 dynes/cm 2 versus 23.3±11.0 dynes/ cm 2 ; P=0.007). This result reveals that cerebral AVMs are a high WSS pathology, which disputes Rossitti and Svendsen's hypothesis that WSS in arteries supplying AVMs is the same as in arteries within normal brain parenchyma.…”
Section: Discussioncontrasting
confidence: 50%
“…5,[8][9][10][11][12] We found that mean flow dropped on average by 29% after a single embolization session and by 75% at the end of all embolization sessions. Interestingly, the drop in flow per session did not correspond to occlusion of an intranidal fistula or the number of pedicles embolized in that single session, suggesting redistribution of flow through remaining compartments of the nidus in the setting of partial embolization, as posited by Kaspera et al 14 On the other hand, mean flow after completion of all embolization sessions correlated with both the total number of pedicles embolized and embolization of a high-flow fistula, with total pedicles embolized remaining predictive in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 62%
“…This QMRA technique has been validated using in vitro and in vivo models and has demonstrated utility in the hemodynamic evaluation of cerebrovascular pathologies and interventions, including extracranial carotid artery stenosis, intracranial angioplasty/stenting, carotid endarterectomy, and extracranial-intracranial bypass. [8][9][10][11][12] Total AVM blood flow was derived based on the aggregate flow within the primary arterial feeders relative to flow in their contralateral counterparts, according to the following equation: …”
Section: Blood Flow Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly in subsequent analysis of patients with both anterior and posterior circulation intracranial stenosis from the WASID trial, angiographic collaterals had a marked influence on stroke risk, with good collaterals significantly reducing risk in those with severe stenosis 19 . Recent data from large vessel flow measurements in carotid disease further support the importance of regional flow by demonstrating that flow compromise in the distal territory measured in the middle cerebral artery territory was more frequently associated with symptomatic presentation, whereas flow decline in the internal carotid alone was not predictive 20 .…”
Section: Discussionmentioning
confidence: 96%